Respons UNESCO terhadap Penghancuran Warisan Budaya Dunia di Suriah - Meydira Shahnaz; Ika Riswanti Putranti; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2017)
The Syrian conflict that started from 2011 brings down various victims. The victims are not only its people but also their cultural objects. In 2015, two Syrian cultural objects which enlisted into World Heritage list, Ancient City of Palmyra and Ancient City of Bosra destructed by conflicted actors. In this circumstances, UNESCO is needed to take mandatory actions towards the issue. This research used qualitative methods alongside with role of international organization concept to explain UNESCO’s response towards the destruction of Palmyra and Bosra. The result of this research indicated that UNESCO as an international organization has managed to fulfill its role in certain phenomena, namely as the arena and actor.